Low Rates of Return to Sport and Reduction in Performance Following Acute Achilles Tendon Ruptures in Athletes Participating in Major League Soccer - James J. Butler MB BCh BAO; Bader Nasir BS; Charles Lin MD; Djani Robertson MD; Alan P. Samsonov BS; John G. Kennedy MD, MCh, MMSc, FFSEM, FRCS (Orth) (Foot & Ankle Orthopaedics, 2024)
Category: Sports; Other Introduction/Purpose: The purpose of this study was to assess outcomes following acute Achilles tendon ruptures (AATR) sustained by athletes participating in the Major League Soccer (MLS). Methods: Athletes participating in the MLS who sustained an AATR were identified using a publicly available database, match reports and injury reports. The years of inclusion was from 2008-2022. Data collected and analysed: player demographics, player position, if surgical intervention was warranted, rates of return to play (RTP), time to return to play, games missed. Pre-injury and post-injury performance outcomes collected and analysed: games played, assists, goals, passes, pass %, crosses, shots, shots on target and shot %. Results: Twenty-six athletes sustained an AATR in the MLS (0.008564 per 10,000 athlete-exposures). The mean age was 25.8±8.4 years and the mean BMI was 22.5±6.6kg/m 2 . There were 15 (57.7%) AATRs sustained by defensive players, 5 (19.2%) AATRs sustained by midfield players, 3 (11.6%) AATR sustained by forwards and 3 (11.6%) AATR sustained by goalkeepers. All athletes (100%) underwent surgical intervention. The mean number of games played prior to injury was 164.7±154.9. The RTP rate to the MLS was 73.1% at mean time of 11.1±5.5 months. The mean number of games missed due to injury was with 30.1±11.7 games. There was a statistically significant decrease in the mean number of games played, goals scored and shots taken following RTP. Conclusion: This current study found that AATRs were an uncommon injury in the MLS with an incidence of 0.008564 per 10,000 athlete-exposures. Sustaining an AATR was associated with a 73.1% return to play rate to the MLS at a mean time of 11.1 ± 5.5 months. There was a statistically significant deterioration in key performance metrics such as mean games played, goals scored and shots taken. This study reinforces the potentially devastating sequelae following AATR in the elite athletic population.